Factors Causing Early Marriage From Sociocultural View in The Working Area of Ketapang Health Center of South Sungkai Regency, North Lampung District in 2023 - Fatmawati, Fatmawati; Yantina, Yuli; Susilawati, Susilawati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Early marriage is still a global problem, around 21% of women in the world get married early, in Indonesia there are 1.2 million early marriages every year. Lampung Province data for 2022, the percentage of early marriage for women is 4.57%, while North Lampung Regency is 9.62%. Early marriage data in the Working Area of the Ketapang Health Center in 2021 reached 17.6% and increased in 2022 to 25.2%. Early marriage will have a negative impact both physically and psychologically. One of the causes of early marriage is sociocultural. The purpose of this research is to know the factors that cause early marriage in terms of socio-culture. This type of research is quantitative and case control research design. The population in this study were all married women in the working area of the Ketapang Health Center, with a sample of 72 people, using proportional random sampling. Statistical test using the chi-square test. The statistical test results showed that the variable ethnicity with p-value = 0.074 , age group p-value = 0.000, school time p-value = 0.000, length of education p-value = 0.004, and last year's activities p-value = 0.000. The results showed that factors related to early marriage included age group, school time, length of education, and last year's activities. Meanwhile, there is no relationship between ethnicity and early marriage. It is hoped that health workers can increase health education to adolescents in schools regarding reproductive health and also the impact of early marriage. Keywords: Early Marriage, Socio-Cultural, Youth